L1, a 3,3′-diindolylmethane-derivative, induced ER stress-mediated apoptosis and suppressed growth through the FLI1/AKT pathway in erythroleukemia HEL cells - Kuang, Yi; Jian, Yong; Wang, Dinghuan; Bai, Lihao; Yu, Kunlin; Wang, Chunlin; Liu, Wuling; Liu, Sheng; Li, Wan; Ben-David, Yaacov; Xiao, Xiao (Frontiers in Pharmacology, 2025)
Introduction3,3′-Diindolylmethane (DIM) is a major phytochemical product derived from ingestion of cruciferous vegetables. As an effective cancer chemopreventive agent, DIM has been used in preclinical and clinical trials. Recently, our group synthesized and modified a novel DIM derivative, L1, and demonstrated its significant antileukemic activities.MethodsMTT assay was used to confirm the inhibition rates and IC50 value of L1 in erythroleukemia HEL cells. Flow cytometry analysis was used to reveal cell cycle arrest and apoptosis. RNAseq data with KEGG pathway enrichment analysis was performed to predict the anticancer mechanism of L1. RT-qPCR and Western blotting were carried out to verify the mechanism in the ER stress-mediated apoptosis and FLI1/AKT pathway. FLI1 knockdown in HEL cells was performed to confirm the mechanism of L1 in the FLI1/AKT pathway. AutoDocking analysis and PPI analysis via the STRING database were used to discover the potential target of L1. HSPA1A knockdown and treatment with HSP70 inhibitor were used to further evaluate the L1 target.ResultsL1 significantly inhibited the growth of erythroleukemia HEL cells, with an IC50 value of 1.15 ± 0.03 µM L1 induced G2/M cell cycle arrest and cell apoptosis. RNA sequencing analysis revealed that differentially expressed genes (DEGs) mainly enriched in protein processing of endoplasmic reticulum (ER). L1 increased the protein expression level of GRP78 (BIP) and the RNA transcription of XBP1 and DDIT3 to induce ER stress-mediated apoptosis. Meanwhile, PPI analysis suggested that HSP70 (HSPA1A and HSPA1B) is a pivotal gene that may be involved in the ER stress. AutoDocking analysis also revealed that L1 may bind to the HSP70 protein (HSPA1A and HSPA1B). The apoptosis rate was reduced by cotreatment of L1 and the Hsp70 inhibitor VER155008. Moreover,the inhibition rate was decreased in the HSPA1A knockdown HEL cells, suggesting that L1-induced apoptosis was related to HSP70 activity. Moreover, FLI1 is a crucial target for mediating cell differentiation, apoptosis, inflammation and displays abnormal expression in HEL cells. Here, we showed that the protein expression levels of FLI1 and AKT/p-AKT decreased with L1 treatment and that the RNA expressions of their downstream genes GATA1, TFRC, GYPA, CDKN1A and CDKN1B were also regulated by L1.ConclusionThis study revealed that the DIM-derivative molecule, L1, induced ER stress-mediated apoptosis and suppressed cell growth by inhibiting the FLI1/AKT pathway in erythroleukemia HEL cells.